Helicopter Money: Should Central Banks Rain Money from the Sky? - Ansgar Belke (Intereconomics, 2018)
Ultra-low interest rates have become an endemic and potentially problematic characteristic of the global economy. Central banks in the euro area, the United States, Japan and Australia have bet on lowering interest rates to increase inflation, but despite their efforts, core inflation remains stubbornly below the desired two per cent. However, central banks have another tool at their disposal that has the potential to stimulate infl ation: helicopter money.
Keywords: 330